Program SI GULA Sebagai Pencegahan Diabetes Mellitus Tipe 2 di Desa Wonorejo - Hadrianti H. D. Lasari; Intania Hikmah Al Farabi; Karina Rusadi; Kusuma Indah Pertiwi; Lailatul Qumariah; Rasti Amanda (Cv. Utility Project Solution, 2023)
The increasing incidence of diabetes mellitus as a non-communicable disease continues to occur worldwide, which can cause organ failure to death. Type 2 diabetes mellitus is diabetes that occurs because the body is unable to use insulin so body weight increases and physical activity decreases. The World Health Organization (WHO) states that the population affected by DM will increase by at least 366 million people in 2030 and based on the results of a WHO survey, Indonesia will be included as the 4th highest country with a population suffering from DM. Based on the community diagnosis, the people of Wonorejo Village RT 10 and 19 are at risk of having type 2 DM with a percentage of sufferers of 18.2% in RT 10 and 3.8% in RT 19. The method used to prevent type 2 DM is a series of SI GULA intervention activities (Exercise, Use Health Information, and Check Blood Sugar) using leaflets and posters as media. The results of this community service show that exercise can reduce blood sugar levels (42.5%) and DM counseling can increase knowledge (38.91%), and exercise can also be a community empowerment movement for preventing and controlling non-communicable diseases.